Arto Der Haroutunian: The Yoghurt Book - D., J.M. (Petits Propos Culinaires, 2024)
Arto Der Haroutunian: The Yoghurt Book: Penguin Books Ltd, Harmondsworth, Middlesex, 1983: 206 pp. paperback, glossary, index, £1.95.